Pendidikan Humanistik dan Emansipatoris dalam Novel Totto-Chan: Kajian Filosofis Futurologis - Alatas, Mochamad Arifin; Suyatno, Suyatno; Sodiq, Syamsul; Mintowati, Mintowati; Nurhadi, Didik; Yuniseffendri, Yuniseffendri (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The humanistic and emancipatory education promoted in Tetsuko Kuroyanagi's novel Totto-Chan: The Little Girl at the Window offers a learning model that is relevant to the challenges of future education in Indonesia. This study aims to explore the application of the concept of humanistic, inclusive, and emancipatory education contained in the novel, and its relevance to 21st-century education in Indonesia. The research method used is a qualitative approach with text analysis, followed by a philosophical study of the concept of education raised in the novel. The results of the study indicate that education based on freedom, inclusivity, and character development at Tomoe Gakuen has the potential to be applied in Indonesian education, by utilizing technology to create more independent, creative, and inclusive learning, and shaping students' characters to face increasingly complex global challenges. In addition, the results of this study also highlight the importance of the role of teachers as facilitators in creating a learning environment that supports the development of 21st-century skills, such as critical thinking, collaboration, and problem solving, as well as developing social empathy in the digital era.